Character Education For Vocational High School (SMK) Students In The Digital Era - Sri Hariati; Susi Anita Patmawati; Hairul Saleh Satrul (International Journal of Education, Vocational and Social Science, 2023)
Education is a process of strengthening and developing human attitudes and behavior as well as the inheritance of knowledge and skills in order to help students reach a level of maturity in their attitudes and thoughts. The development of technology and information in today's digital era is very fast and complex which can actually have a negative impact on the formation of student character which is boomeranging in the world of education. This research will use a combined qualitative and quantitative research method with the research location being conducted in Southeast Sulawesi, Kolaka Regency (SMKN 7 Kolaka Timur) using a descriptive study that provides an overview of the subjects and objects of the research. From the results of the study, it was found that there were positive and negative impacts on character education in the current digital era. Character education innovations in the digital era have negative impacts experienced by teachers and students in the 21st century. Based on this, the researcher provides suggestions in this study that in dealing with the positive and negative impacts of character education in the digital era, several solutions can be applied including: (1) Learning about digital ethics, (2) Limiting layer time, (3) Education about digital literacy, (4) Online security and privacy, (5) Development of social and emotional skills, and (6) Collaboration with parents and the community.